Activity‐Based Kinome Profiling Using Chemical Proteomics and ATP Acyl Phosphates. Issue 3 (23rd August 2019) - Franks, Caroline E.; Hsu, Ku‐Lung
Abstract: Human kinases are a large family of proteins (500+) that catalyze ATP‐dependent phosphorylation of protein and metabolite substrates to regulate diverse facets of cell biology. Dysregulation and mutations of protein kinases are linked to human disease, providing opportunities for developing pharmacological agents as potential therapy. Assessing the selectivity of pharmacological compounds targeting this enzyme class is critical given that off‐target activity of kinase inhibitor drugs may result in toxicity. This set of protocols outlines use of ATP acyl phosphate activity–based probes to evaluate the potency and selectivity of kinase inhibitors via fluorescent gel– and mass spectrometry–based detection methods. These competitive chemical proteomic assays can evaluate engagement of >200 native kinase targets directly in complex proteomes. © 2019 by John Wiley & Sons, Inc.